Parental High-Fat High-Sugar Diet Intake Programming Inflammatory and Oxidative Parameters of Reproductive Health in Male Offspring - Sertorio, Marcela Nascimento; César, Helena; de Souza, Esther Alves; Mennitti, Laís Vales; Santamarina, Aline Boveto; De Souza Mesquita, Leonardo Mendes; Jucá, Andréa; Casagrande, Breno Picin; Estadella, Debora; Aguiar, Odair; Pisani, Luciana Pellegrini (Frontiers in Cell and Developmental Biology, 2022)
Parental nutrition can impact the health of future generations, programming the offspring for the development of diseases. The developing germ cells of the offspring could be damaged by the maternal or the paternal environment. The germ cells in development and their function could be affected by nutritional adversity and therefore, harm the health of subsequent generations. There is a need for studies that address the combined effects of diets with a high-fat and high-sugar (H) content by both progenitors on male reproduction. In this context, our study evaluated the inflammatory response that could be associated to oxidative stress on sperm parameters in testis and epididymis of adult offspring. 90 days-old male rats were divided according to the combination of the parental diet: C (control paternal and maternal diet), HP (H paternal diet and control maternal diet), HM (H maternal diet and control paternal diet) and HPM (H paternal and maternal diet).We evaluated serum levels of testosterone and FSH, the gene expression of StAR and 17β-HSD; testicular and epididymal levels of TNF-α, IL-6, IL-10 and IL-1β; testicular and epididymal activity of SOD, CAT and GST; the oxidative markers MDA and PC; the daily sperm production, sperm transit time, and sperm morphology. The testicular inflammatory response, the oxidative balance and the daily sperm production of the offspring were affected by the maternal diet; paternal diet influenced serum testosterone levels, and lower daily sperm production was exacerbated by the interaction effect of both parental intake of high-fat high-sugar diet. There was isolated maternal and paternal effect in the antioxidant enzyme activity in the cauda epididymis, and an interaction effect of both parents in protein oxidative marker. Maternal effect could also be observed in cytokine production of cauda epididymis, and no morphological effects were observed in the sperm. The potential programming effects of isolated or combined intake of a high-fat high-sugar diet by the progenitors could be observed at a molecular level in the reproductive health of male offspring in early adulthood.